Correction: Unsupervised capture and profiling of rare immune cells using multi-directional magnetic ratcheting. Issue 23 (13th November 2018) - Murray, Coleman; Miwa, Hiromi; Dhar, Manjima; Park, Da Eun; Pao, Edward; Martinez, Jessica; Kaanumale, Sireesha; Loghin, Evelina; Graf, John; Raddassi, Khadir; Kwok, William W.; Hafler, David; et al.
Abstract : Correction for 'Unsupervised capture and profiling of rare immune cells using multi-directional magnetic ratcheting' by Coleman Murray et al., Lab Chip, 2018, 18, 2396–2409.